X-Band Microstrip Bandpass Filter Design using Square Loop Resonator and Defected Ground Structure - E. Edwar; M.R. Yusron; Dharu Arseno (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2020)
Filter is an important part in telecommunication system including in radar system. To get the better performance in selecting the signal, a ftlter must have a good Q-Factor. In this paper, an investigation of a ftlter design for synthetic radar has been successfully done. This ftlter has been designed to work at x-band using square loop resonator (SLR). A Defected Ground Structure (DGS) has been implemented to this work to increase the Q-factor of the ftlter. The result of measurement getting that the center frequency at 9.51 GHz with the bandwidth 610 MHz and PCB size of this ftlter is 22 mm x 16 mm.